Vulvar cancer in a patient with long-lasting premalignant lesions in the genital area: easily overlooked and difficult to diagnose – a case report and literature review - Szatko, Alicja; Kacperczyk-Bartnik, Joanna; Bartnik, Paweł; Dobrowolska-Redo, Agnieszka; Derlatka, Paweł; Kalinowska, Monika; Marczuk , Hanna; Romejko-Wolniewicz, Ewa (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Vulvar intraepithelial lesions are a heterogenic group of diseases, which can be easily misdiagnosed. The case of a 61-year-old woman with a history of genital intraepithelial lesions and infection with HPV is presented. Her main complaint was vulvar pruritus. Vulvoscopy revealed the presence of two skin lesions: the first one had the morphology of lichen sclerosus, and the second of a Bowenoid lesion. The biopsy of the first lesion revealed vulvar intraepithelial neoplasia, whereas cells of squamous vulvar cancer were identified in the second lesion. After staging, the patient was advised to undergo hemivulvectomy and lymphadenectomy. The coexistence of morphologically diverse vulvar skin lesions may cause difficulties with diagnosis and the selection of an adequate treatment. Long-term follow-up and regular examination are essential for diagnosis of vulvar malignancies in the early stage.